INVESTIGATION OF FUNGI SPORES CONCENTRATION IN NIĞDE ATMOSPHERE (TURKEY) - Çeter, Talip; Bayar, Esin; Eltajouri, Mohamed Nurı; İşlek, Cemil; Pinar, Nur Münevver (Ankara Üniversitesi, 2020)
Atmospheric fungi spores investigated in Niğde province with the help of Burkard volumetric trap between January 2014 -December 2014. As total of 70 561 spores belonging to 39 Fungi taxa were counted. The taxa which were observed are the following Cladosporium, Alternaria, Melanomma, Leptosphaeria, Ustilago, Pleospora, Exosporium, Penicillium/Aspergillus, Elipsoidal basidyospores, Epicoccum, Drechslera, Stemphylium, Multi-septate ascospores, 1-septate ascospores, Myxomycetes, Pithomyces, Torula, Didymella, Puccinia, Chaetomium, Curvularia, Non-septate ascospores, Oidium, Nigrospora, Periconia, Diatrypaceae, Venturia, Arthrinium, Xylaria, Agrocybe, Fusarium, Botrytis, Peronospora, Coprinus, Sporormiella, Tetracoccosporium, Exosporiella, Melanospora and Boletus. The concentration of spores which was determined in the atmosphere was 69,46% Cladosporium, 7,21% Alternaria, 2,98% Melanomma, 2,69% Leptosphaeria, 2,28% Ustilago, 2,15% Pleospora, 1,98% Exosporium, and the remaining 11.09% belong to 32 taxa which named as an others.
Keywords: Structural Biology; Yapısal Biyoloji; Allergy; Fungi spores; Niğde; Turkey